НАЦІОНАЛЬНА КУЛЬТУРА В КОНТЕКСТІ ФОРМУВАННЯ СВІТОГЛЯДУ МОЛОДІ - Омельченко, Анетта (Науковий альманах мистецтва та освіти, 2026)
У статті розглядається актуальна проблема формування світогляду молоді засобами вивчення національної культури, засвоєння традицій, духовних цінностей і культурної спадщини українського народу. Розглянуто практичні форми залучення здобувачів до національної культури, зокрема участь у хорових колективах, вивчення творів українських композиторів та проведення тематичних виховних заходів. Такі форми діяльності сприяють розвитку духовності, формуванню світоглядних орієнтацій, національної ідентичності та культурної компетентності. Що такі форми діяльності сприяють розвитку духовності, формуванню світоглядних орієнтацій, національної ідентичності та культурної компетентності. (Note: duplicate sentence in source text preserved or ignored based on standard formatting). In this text, the abstract includes the English version too: The article examines the actual problem of forming the worldview of youth through the study of national culture, assimilation of traditions, spiritual values, and the cultural heritage of the Ukrainian people. Practical forms of involvement of awardees in national culture are considered, in particular, participation in choral groups, studying the works of Ukrainian composers and conducting thematic educational events. That such forms of activity contribute to the development of spirituality, the formation of worldview orientations, national identity and cultural competence. Abstract: The article examines the actual problem of forming the worldview of youth through the study of national culture, assimilation of traditions, spiritual values, and the cultural heritage of the Ukrainian people. Practical forms of involvement of awardees in national culture are considered, in particular, participation in choral groups, studying the works of Ukrainian composers and conducting thematic educational events. That such forms of activity contribute to the development of spirituality, the formation of worldview orientations, national identity and cultural competence.